2018
DOI: 10.1016/j.cophys.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Beyond sex differences: short and long-term implications of motherhood on women’s health

Abstract: Physiological changes during pregnancy influence many aspects of maternal health Steroid and peptide hormones are elevated dramatically during gestation Reduced grey matter is detected in multiple regions after motherhood Physiological changes with motherhood are detected years after giving birth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Further, the influence of sex-hormone exposure on the brain may be genotype-specific, with more prominent effects of timing and dosage of hormone replacements in women with a genetic risk for AD. These findings represent an important contribution to the understudied field of female-specific factors and women's brain aging (Galea et al, 2018), which may complement prospective longitudinal studies on women's brain health and epidemiological sex-differences in AD.…”
Section: Discussionmentioning
confidence: 63%
“…Further, the influence of sex-hormone exposure on the brain may be genotype-specific, with more prominent effects of timing and dosage of hormone replacements in women with a genetic risk for AD. These findings represent an important contribution to the understudied field of female-specific factors and women's brain aging (Galea et al, 2018), which may complement prospective longitudinal studies on women's brain health and epidemiological sex-differences in AD.…”
Section: Discussionmentioning
confidence: 63%
“…The use of large datasets does, however, enable the identification of subtle effects that could go undetected in smaller samples. Although parity may explain only a small portion of the variance in brain aging, the current findings represent an important part of the wider picture of women's brain aging, as well as sex differences in risk factors and disease (9,30).…”
Section: Discussionmentioning
confidence: 68%
“…In the postpartum period, regional gray matter increases have been found in the amygdala, hypothalamus, and prefrontal cortex (6). Postpartum regional reductions have also been reported (7)(8)(9), some of which are positively related to maternal attachment (8). While some maternal brain changes revert during the postpartum period, others extend well beyond this phase (1,7,8,10) and may influence the course of neurobiological aging later in life.…”
Section: Maternal Brain Adaptations Have Been Found Across Pregnancy mentioning
confidence: 99%
“…Despite the known sex differences in prevalence, as well as symptoms, severity, and treatment responses [25,26], there has been limited focus on how sex-specific immunology affects brain aging [27,25]. Recent studies have shown that pregnancy-related endocrinological fluctuations influence neural plasticity and brain structure in animals [28,29,30,31,32] and humans [33,34,35,36], and that biological processes related to menopause can have significant effects on brain health [37]. During pregnancy and menopause, the female immune system undergoes substantial changes [38,39], and evidence suggests that the immune regulations that occur during these major transitional phases may play an important part in women's brain aging trajectories [40,41,42].…”
Section: Introductionmentioning
confidence: 99%